THE ISSUES OF SERVICMEN DISCIPLINE AND ADAPTACION - Nadoyan, A.A.; Minasyan , G. H. (Modern Psychology, 2022)
The article introduces the requirements of RA Armed Forces presen- ted to servicemen. Discipline is the strict and mandatory maintenance of rules regulated by laws and military orders and set by the commanders. The purpose of the research is to study military discipline, the causes and effects of disorder as well as its results, since it is based on the awareness of military duty and personal responsibility of servicemen. The objectives of our planned continuous research are to observe the approaches to the issue under discussion in scholarly literature, to investigate the peculiarities of discipline and disorder among the examined servicemen, their ways of expression as well as causes and effects. The topicality of the issue is determined by the importance of the discipline of servicemen and accomplishment of the objectives mentioned above. The hypothesis of the research is that the more flexible is the adaptability of the serviceman during the military service, the more effective he is in complying with the requirements and regulations of the military service. The research has been carried out among 200 military servicemen. To investigate this issue the corresponding psychological assessments methods have been applied: test method, psychological conversation, observation and case study.
Keywords: serviceman; discipline; disciplinary penalty; encouragement; adaptation